Fontan Revision: Presurgical Planning Using Four-Dimensional (4D) Flow and Three-Dimensional (3D) Printing. Issue 2 (March 2019) - Carberry, Thomas; Murthy, Raghav; Hsiao, Albert; Petko, Colin; Moore, John; Lamberti, John; Hegde, Sanjeet
Pulmonary arteriovenous malformations (AVMs) can be a complication of certain postoperative Fontan patients whose hepatic venous blood return is not distributed evenly to both lungs. A ten-year-old female, who had previously undergone staged single ventricle palliation for complex congenital heart disease, underwent a Fontan revision due to significant left-sided pulmonary AVMs and increasing arterial oxygen desaturation. The combination of four-dimensional flow cardiac magnetic resonance imaging and three-dimensional printing enabled presurgical planning for a Fontan takedown and diversion of hepatic venous flow to the azygous vein that resulted in significant clinical improvement.